2014
DOI: 10.2174/13816128113199990036
|View full text |Cite
|
Sign up to set email alerts
|

Hypusine Modification of the Ribosome-binding Protein eIF5A, a Target for New Anti-Inflammatory Drugs: Understanding the Action of the Inhibitor GC7 on a Murine Macrophage Cell Line

Abstract: Inflammation is part of an important mechanism triggered by the innate immune response that rapidly responds to invading microorganisms and tissue injury. One important elicitor of the inflammatory response is the Gram-negative bacteria component lipopolysaccharide (LPS), which induces the activation of innate immune response cells, the release of proinflammatory cytokines, such as interleukin 1 and tumor necrosis factor α(TNF-α), and the cellular generation of nitric oxide (NO) by the inducible nitric oxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Indeed, as shown in Figure 5 B, UV irradiation increased the amount of Ser-51 phosphorylated eIF2. Interestingly, treatment with GC7 alone also caused an increase of 80S ribosomes and a decrease of the polysomal fraction, similar to what was observed by other authors [ 40 ]. However, in this case, we did not observe any increase of eIF2α phosphorylation, contrary to what reported by other researchers on other cell lines [ 41 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, as shown in Figure 5 B, UV irradiation increased the amount of Ser-51 phosphorylated eIF2. Interestingly, treatment with GC7 alone also caused an increase of 80S ribosomes and a decrease of the polysomal fraction, similar to what was observed by other authors [ 40 ]. However, in this case, we did not observe any increase of eIF2α phosphorylation, contrary to what reported by other researchers on other cell lines [ 41 ].…”
Section: Resultssupporting
confidence: 89%
“…Our results are consistent with those of other authors showing that eIF5A is required for proper p53 expression in response to Actinomycin D [ 23 ]. Although the increase of p53 under stress conditions may be in part attributed to reduced protein turnover, there is also an important contribution of de novo translation [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Indeed, we observed that a brief exposure of HCT-116 cells to the protein synthesis inhibitor cycloheximide reduced the induction of p53 protein after UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gutierrez et al [23] reported similar activity of eIF5A in S. cerevisiae , including a model of eIF5A bound to 80S ribosome with its hypusine residue pointing to the peptidyl transferase center, supporting the notion that eIF5A has a critical role in the translation elongation of polyproline motifs. All living organisms contain either EF-P, or aIF5A or eIF5A and this factor(s) is one of the few universally conserved translation factors [24]. Furthermore, EF-P and aIF5A/eIF5A have analogous modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The abolishment of LH/hCG-induced increases in LRBP mRNA and protein expression by inhibition of eIF5A hypusination as shown in the present study is consistent with previous reports using other systems showing the effect of hypusination inhibition on transcription and translation. For example, de Almeida et al have reported that inhibition of eIF5A hypusination by GC7 inhibits mRNA expression of inflammatory mediators [28] and Li et al [11] have shown that eIF5A affects translation elongation in U2OS (human osteosarcoma), COS7, and RDG3 cells.…”
Section: Discussionmentioning
confidence: 99%